Unilateral lichen planus: A rare case report - Bajpai, Manas (Medknow Publications & Media Pvt Ltd, 2014)
Oral lichen planus (OLP) is a mucocutaneous disease with well-established clinical and histopathological features. It has a prevalence of approximately 1%. The etiopathogenesis is poorly understood. The annual malignant transformation is less than 0.5%. There are no effective means to either predict or to prevent such event. Clinically, OLP present as bilateral symmetrical lesion and hence lichen planus isolated to a single oral site other than the gingiva is very uncommon. On the other hand lichenoid reaction (LR) are the lesions which are similar clinically and histopathologically with OLP, but they are induced with some drug reaction and usually they do not show bilateral pattern like lichen planus. We reported a very uncommon case of unilateral lichen planus which was clinically diagnosed as LR, but in the absence of any cause-effective relationship biopsy was taken for histopathological examination Histopathologically, LR cannot be differentiated with OLP, so the final diagnosis was made on the immunohistochemical ground.